Lipoprotein (a) as an independent risk factor for myocardial infarction in patients with common hypercholesterolaemia. Issue 3 (March 1993) - Watts, G F; Kearney, E M; Taub, N A; Slavin, B M
Abstract : AIMS: To examine whether lipoprotein (a) (Lp(a)) increases the risk of myocardial infarction (MI) in patients with common hypercholesterolaemia. METHODS: 15 middle aged men with common hypercholesterolaemia (mean serum low density lipoprotein (LDL) cholesterol 4.94 mmol/l, SD 1.0) and a history of MI were selected consecutively from referrals to a lipid clinic. A control group that had not sustained an MI and with similar age, sex, cigarette smoking and blood pressure characteristics was also selected from the same clinic. Serum cholesterol, triglyceride, LDL cholesterol, high density lipoprotein cholesterol, apolipoproteins AI and B and Lp(a) were measured in both groups. Lp(a) was assayed by immunoturbidity. RESULTS: The serum concentration of Lp(a) was significantly higher in patients with MI (geometric mean 0.64 (95% confidence interval 0.36 to 1.14) v 0.30 (0.21 to 0.42) g/l, p = 0.02), but there were no significant differences in other variables. Stepwise logistic regression analysis showed that Lp(a) was the only significant predictor of MI (p < 0.02). The odds ratio of MI (adjusted for age, smoking, blood pressure and apolipoprotein B) for an Lp(a) of > 0.57 g/l was 16.5, 95% confidence interval 2.3 to 125.4 (p = 0.001). CONCLUSION: In middle aged men with common hypercholesterolaemia the serum concentration of Lp(a) is a powerful and independent risk factor for MI. Lp(a) should probably be routinely measured in all patients referred to a lipid clinic.